Teaching on the Run – Learning on the Go (Training and Practice : Journal of Educational Sciences, 2019)
In an attempt to prepare students to meet the demand of the future workforce, and also to address the dropout crisis, educators are looking for new ways to integrate virtual worlds into the curricula. Digital economy finds its way to the tech-savvy youth. The number of computers, smartboards, and all kinds of widgets serving digital education are on the rise. Still, on the most part, our academic institutions continue to follow a 19th-century path based on rote learning and high-stakes testing. The paper intends to summarize some of the dominating notions that define the prevailing narratives of these issues. It also aims to explore the discrepancy between the imagined and the real learning environment while shedding light on the 2015 PISA results that show that technology alone will neither improve pupils' achievement nor will it help prepare them for the 21st-century labor market needs.